Akad Sukuk Mudharabah dan Praktiknya di Indonesia dan Negara Kuwait - Fitri, Desi Elisa; Ahmarani, Putri; Hrp, Khairunnisa Aulia; Nst, Mhd Khairul Anhar; Pratama, M. Aldi; Batubara, Maryam (JSE: Jurnal Sharia Economica, 2025)
This study aims to examine and compare the practice of implementing mudharabah sukuk contracts in Indonesia and Kuwait as two countries that are actively developing sharia financial instruments. Mudharabah sukuk is an investment instrument based on profit sharing between capital owners (shahibul maal) and business managers (mudharib), which does not contain elements of usury and gharar. The method used in this study is a literature study, by examining various secondary sources such as scientific articles, government regulations, financial institution reports, and other academic publications. The results of the study show that Indonesia has built a fairly mature mudharabah sukuk regulatory system through the active role of the Financial Services Authority (OJK) and the National Sharia Council (DSN-MUI), although it still faces challenges in terms of public education and secondary market development. On the other hand, Kuwait has a more integrated regulatory structure and sharia standards based on international guidelines such as AAOIFI, but is still limited in issuing mudharabah sukuk due to technical and market constraints. This comparison shows that both countries have their own strengths and weaknesses in developing mudharabah sukuk, which can be a cross-country learning in an effort to strengthen the global sharia financial market.